Resales of Offshore Securities into the United States: Evaluating the Overvaluation Risk to U.S. Investors - Stephen J. Choi (Washington University Law Quarterly, 2000)
This Article furnishes evidence on the offering discount consistent with the hypothesis that foreign investors were in fact unable to engage in resales ahead of the U.S. secondary market reaction to a Regulation S offering.
Keywords: Securities -- International regulation; Foreign banks; Securities industry; Securities law